RhoA/ROCK2 signaling pathway regulates Mn-induced alterations in tight junction proteins leading to cognitive dysfunction in mice - Yan Ma; Honggang Chen; Yuxin Jiang; Diya Wang; Michael Aschner; Wenjing Luo; Peng Su (Current Research in Toxicology)
Elevated manganese (Mn) exposure has been implicated in a broad spectrum of neurological disorders, including motor dysfunction and cognitive deficits. Previous studies have demonstrated that Mn induces neurotoxicity by disrupting the integrity of the blood–brain barrier (BBB), a critical regulator in maintaining central nervous system homeostasis and a contributing factor in the pathogenesis of numerous neurological disorders. However, the precise molecular mechanisms underlying Mn-induced BBB disruption and its role in facilitating neurotoxicity remain incompletely understood. The primary objectives of this study were to elucidate the mechanisms underlying the relationship between Mn exposure and BBB tight junction proteins (TJPs), and to further investigate potential neuroprotective strategies for mitigating Mn-induced cognitive impairments. In this investigation, we developed Mn exposure models utilizing both murine subjects and cell culture systems to elucidate the mechanisms underlying TJPs involvement and to assess the potential neuroprotective effects of gastrodin (GAS), a bioactive compound extracted from traditional Chinese medicine. Our findings revealed a significant reduction in TJPs expression, both in vivo and in vitro, in Mn-induced BBB disruption. The overexpression of Occludin (OCLN), a crucial component of TJPs, mitigated Mn-induced BBB damage. GAS administration effectively attenuated Mn-induced disruption of the BBB, enhanced the expression of TJPs, and mitigated Mn-induced cognitive dysfunctions, potentially through the modulation of the RhoA/ROCK2 signaling pathway. This research sought to advance our understanding of the molecular pathways involved in Mn-mediated BBB disruption and to identify novel therapeutic approaches for mitigating the deleterious effects of Mn exposure on cognitive function.